Opposite effects of Co and Cu dopants on the catalytic activities of birnessite MnO2 catalyst for low-temperature formaldehyde oxidation - Yusuf, Abubakar; Sun, Yong; Ren, Yong; Snape, Colin; Wang, Chengjun; Jia, Hongpeng; He, Jun (American Chemical Society, 2020)
Defect engineering is an effective strategy to enhance the activity of catalysts for various applications. Herein, it was demonstrated that in addition to enhancing surface properties via doping, the influence of dopants on the surface-intermediate interaction is a critical parameter that impacts the catalytic activity of doped catalysts for low-temperature formaldehyde (HCHO) oxidation. The incorporation of Co into the lattice structure of δ-MnO2 led to the generation of oxygen vacancies, which promoted the formation of surface active oxygen species, reduced activation energy, and enhanced catalytic activity for low-temperature oxidation of HCHO. On the contrary, Cu doping led to a drastic suppression of the catalytic activity of δ-MnO2, despite its enhanced redox properties and slight increase in the surface concentration of active oxygen species, compared to pristine δ-MnO2. Diffuse reflectance infrared Fourier transform analysis revealed that in the presence of Cu, carbonate intermediate species accumulate on the surface of the catalysts, leading to partial blockage of active sites and suppression of catalytic activity.